Pelatihan manajemen pemasaran dan laporan keuangan umkm usaha kerajinan Desa Sidomukti Kabupaten Magetan - Silaturahmi, Gati; Widiasmara, Anny (Nur Science Institute, 2022)
In addition to being a profitable business, the Batik business can also preserve the culture of the Indonesian nation. Problems faced by the Batik Mukti Rahayu Joint Business Group (KUBE) in Sidomukti Village, Magetan Regency, which houses 22 batik artisans, marketing has only been limited to their circles or the surrounding community. In addition, KUBE's financial reports are done manually, so KUBE has not predicted its financial capacity. Seeing this, the 2021 Innovation Talent Team will conduct marketing training and operate a simple cash flow application. The method used is field observations, data collection, marketing training, and simple cash flow applications to make financial reports. These marketing training results are that Batik Mukti Rahayu craftsmen (KUBE) in Sidomukti Village, Plaosan District, Magetan Regency already have an Instagram account and a shop at Shopee. It can operate a simple cash flow application for financial reports. The